Sensitivity of VOF simulations of the liquid jet breakup to physical and numerical parameters. (10th September 2016) - Grosshans, H.; Movaghar, A.; Cao, L.; Oevermann, M.; Szász, R.-Z.; Fuchs, L.
Highlights: The primary breakup of a liquid jet is analyzed numerically. A recently developed VOF formulation is applied for the first time to this case. The methodology showed a high accuracy. The flow physics is discussed depending on the fluid properties and injection conditions. Results are compared to data obtained through the One-Dimensional Turbulence model. Abstract: In this paper the characteristics of the primary breakup of a liquid jet is analyzed numerically. We applied the Volumes of Fluids (VOF) approach utilizing the Direction Averaged Curvature (DAC) model, to estimate the interface curvature, and the Direction Averaged Normal (DAN) model, to propagate the interface. While being used for the first time to predict liquid atomization, this methodology showed a high accuracy. The influence of varying the fluid properties, namely liquid-gas density and viscosity ratio, and injection conditions is discussed related to the required grid resolution. Resulting droplet sizes are compared to distributions obtained through the One-Dimensional Turbulence (ODT) model.